Land-Use Changes and Food Insecurity around Oil Palm Plantations: Evidence at the Village Level - Sudrajat, Jajat; Suyatno, Adi; Oktoriana , Shenny (Forest and Society, 2021)
Land conversion of oil palm plantations in the villages of West Kalimantan has caused drastic changes in how farmers fulfill their basic household needs. One such change affects farmers’ food security. This study aimed to explain the deterioration of food self-sufficiency at the village level due to the pressure to use residual pockets of land for oil palm cultivation. The collected evidence was analyzed through an assessment of their residual pockets of land in a single village. A case study survey collected data from July until September 2019 in the village of Batu Barat, district of Kayong Utara, West Kalimantan Province, Indonesia. The study utilized 70 family heads as samples for interviews. They were selected through a simple random sampling technique. We used descriptive quantitative and qualitative methods in our investigation. The results confirmed that the current utilization of the village’s residual lands actually entails even greater food insecurity for farmers, as exemplified by a sizeable decrease in rice fields to merely an estimated 0.59 hectares per household. By contrast, the land utilized by independent smallholders of oil palm cultivation increased to an average of approximately 0.67 hectares per household. This land conversion not only exacerbated food-farmland availability but